Corporation and the Federal Income Tax: Transfers to a Controlled Corporation - Boris I. Bittker (Washington University Law Quarterly, 1959)
This Article will deal with transfers under section 351. This section is of particular importance when individual proprietorships and partnerships are incorporated. It also embraces the transfer of property to a previously organized corporation by its controlling shareholders.
Keywords: Corporate taxes; Income tax -- United States